Pharmacological interactions from the leaves of Maytenus macrocarpa "chuchuhuasi" with inhibitory and stimulating bowel motility drugs - Meléndez-Espíritu , S. (2013)
Objectives: To determine the possible pharmacological interactions from the leaves of Maytenus macrocarpa with inhibitory and stimulating bowel motility drugs. Methods: We used 110 male albino mice with average weight of 25g, Arbos and others method was applied. Activated charcoal was administered at 5 % at dose of 0.1ml/10g, as an intestinal marker. The experimental groups included 0.1 ml/10 g of distilled water, leave extract of M. macrocarpa 1 (500mg/kg), leave extract of M. macrocarpa 2 (3000 mg/kg), 1,5mg/kg of atropine, 5mg/kg of loperamide, 0.4mg/kg of neostigmine, 10mg/kg of metoclopramide, leave extract of M. macrocarpa 1 with metoclopramide, leave extract of M. macrocarpa 1 with loperamide, leave extract of M. macrocarpa 2 with metoclopramide and leave extract of M. macrocarpa 2 with loperamide. The statistical validation was based on Wilconxon, ANOVA and Tukey test. Results: The intestinal charcoal run percentage was 27.04, 34.15, 31.66, 25.57, 15.89, 43.30, 33.99, 32.40, 27.9, 49.34 and 25.36 respectively. The ANOVA test result in p= 0.0007. The Tukey test indicated p <0.05 versus the control group for neostigmine, loperamide, and the interaction between leave extract of M. macrocarpa 2 with metoclopramide, for the last the Wilcoxon test result in p <0.05. Conclusions: It was observed antagonism drug interactions on gastrointestinal motility between leaves extract of M. macrocarpa with loperamide and synergism interactions with metoclopramide.